Avaliação do desenvolvimento neuropsicomotor em crianças na rede básica de saúde utilizando o teste de Denver II: identificação de fatores de risco materno - Cunha, Hilton Luiz da (2008)
Alterations in the neuropsychomotor development of children are not rare and can manifest themselves with varying intensity at different stages of their development. In this context, maternal risk factors may contribute to the appearance of these alterations. A number of studies have reported that neuropsychomotor development diagnosis is not an easy task, especially in the basic public health network. Diagnosis requires effective, low-cost, and easy - to-apply procedures. The Denver Developmental Screening Test, first published in 1967, is currently used in several countries. It has been revised and renamed as the Denver II Test and meets the aforementioned criteria. Accordingly, the aim of this study was to apply the Denver II Test in order to verify the prevalence of suspected neuropsychomotor development delay in children between the ages of 0 and 12 months and correlate it with the following maternal risk factors: family income, schooling, age at pregnancy, drug use during pregnancy, gestational age, gestational problems, type of delivery and the desire to have children. For data collection, performed during the first 6 months of 2004, a clinical assessment was made of 398 children selected by pediatricians and the nursing team of each public health unit. Later, the parents or guardians were asked to complete a structured questionnaire to determine possible risk indicators of neuropsychomotor development delay. Finally the Denver II Developmental Screening Test (DDST) was applied. The data were analyzed together, using Statistical Package for Social Science (SPSS) software, version 6.1. The confidence interval was set at 95%. The Denver II Test yielded normal and questionable results. This suggests compromised neuropsychomotor development in the children examined and deserves further investigation. The correlation of the results with preestablished maternal risk variables (family income, mother s schooling, age at pregnancy, drug use during the pregnancy and gestational age) was strongly significant. The other maternal risk variables (gestational problems, type of delivery and desire to have children) were not significant. Using an adjusted logistic regression model, we obtained the estimate of the greater likelihood of a child having suspected neuropsychomotor development delay: a mother with _75 4 years of schooling, chronological age less than 20 years and a drug user during pregnancy. This study produced two manuscripts, one published in Acta Cirúrgica Brasileira , in which an analysis was performed of children with suspected neuropsychomotor development delay in the city of Natal, Brazil. The other paper (to be published) analyzed the magnitude of the independent variable maternal schooling associated to neuropsychomotor development delay, every 3 months during the first twelve months of life of the children selected.. The results of the present study reinforce the multifactorial characteristic of development and the cumulative effect of maternal risk factors, and show the need for a regional policy that promotes low-cost programs for the community, involving children at risk of neuropsychomotor development delay. Moreover, they suggest the need for better qualified health professionals in terms of monitoring child development. This was an inter- and multidisciplinary study with the integrated participation of doctors, nurses, nursing assistants and professionals from other areas, such as statisticians and information technology professionals, who met all the requirements of the Postgraduate Program in Health Sciences of the Federal University of Rio Grande do Norte